Comparative Analysis of the Global Banking System: A Study of the American and Chinese Banking Regulations - Yao Jinfang; Hisham Noori Hussain Al-Hashimy; Waleed Noori Hussein; Haider Noori Hussain (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article outlines the international financial system and compares Chinese and US banking rules. This study will compare these two economic powerhouses’ monetary, regulatory, and organisational strategies. Global banking has a problem despite its relevance to economic growth and financial management. Different nations restrict their industries, making them less productive and efficient. Thus, decision-makers, regulators, and financial institutions must understand the US-Chinese banking system similarities and differences. This study examines US and Chinese banking rules, how they affect financial stability, and lessons or best practices that could be implemented abroad. This study compares qualitative and quantitative approaches. It requires data, regulatory, and research analysis. Case studies and interviews with industry professionals and officials will help us learn. US and Chinese banks appear to have undertaken considerable regulatory adjustments after the global financial crisis. The Dodd-Frank Act increases US risk management and transparency. China improved financial stability and oversight by strengthening capital adequacy laws and encouraging deleveraging. Following the analysis, banking regulation improved: 1. Encourage international policymaker-regulator interaction and knowledge-sharing. 2. This study helps policymakers understand the global banking system.